The Appointment of Bishops in Early-Modern Portugal (1495–1777) - Paiva, José Pedro (The catholic historical review, 2011)
The author explains the theoretical model that was used in early-modern Portugal for appointing bishops, based on original research of 505 episcopal appointments. The author argues that the model enabled monarchs to better control the prelates and consequently the Portuguese Church, which reinforced the power of the state over the spiritual sphere in the realm.